2020
DOI: 10.1038/s41380-020-0683-y
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus accumbens fast-spiking interneurons in motivational and addictive behaviors

Abstract: The development of drug addiction is associated with functional adaptations within the reward circuitry, within which the nucleus accumbens (NAc) is anatomically positioned as an interface between motivational salience and behavioral output. The functional output of NAc is profoundly altered after exposure to drugs of abuse, and some of the functional changes continue to evolve during drug abstinence, contributing to numerous emotional and motivational alterations related drug taking, seeking, and relapse. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 237 publications
(161 reference statements)
0
38
0
1
Order By: Relevance
“…CP-AMPARs are glutamate-gated ion channels lacking the post-transcriptionally edited GluA2 subunit ( Lalanne et al, 2018 ). Although developmentally regulated, GluA2-lacking CP-AMPARs mediate fast excitatory transmission at privileged synaptic loci within IN-embedded microcircuits ( Hu et al, 2014 ; Schall et al, 2020 ). CP-AMPARs exhibit greater single-channel conductance, inward rectification, and sharp activation-deactivation kinetics that confer specialized synaptic properties ( Twomey et al, 2017 , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…CP-AMPARs are glutamate-gated ion channels lacking the post-transcriptionally edited GluA2 subunit ( Lalanne et al, 2018 ). Although developmentally regulated, GluA2-lacking CP-AMPARs mediate fast excitatory transmission at privileged synaptic loci within IN-embedded microcircuits ( Hu et al, 2014 ; Schall et al, 2020 ). CP-AMPARs exhibit greater single-channel conductance, inward rectification, and sharp activation-deactivation kinetics that confer specialized synaptic properties ( Twomey et al, 2017 , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…We used the NAc because behavioral phenomena that occur METH self-administration (METH SA) are thought to be regulated by interconnections between distinct brain regions that include that structure [ 113 ]. Neuroplastic changes in the NAc are thought to participate in the development and maintenance of drug-taking behaviors [ 114 ]. We found, for the first time, that rats that continued to take METH compulsively exhibited differential DNA hydroxymethylation in comparison with both control and nonaddicted rats [ 55 ].…”
Section: Potassium Channels and Methamphetamine Use Disordermentioning
confidence: 99%
“…We found that FS-neurons in the NAc had reduced firing rates after tamoxifen administration and this correlated with a decrease in local theta power. In the NAc area, FS interneurons modulate principal neurons through its powerful and sustained feedforward inhibition [40,41]. PV expressing interneurons, which constitute 1-2% of NAc neurons, have particular firing properties and are classified as FS-neurons [40,42].…”
Section: Discussionmentioning
confidence: 99%
“…In the NAc area, FS interneurons modulate principal neurons through its powerful and sustained feedforward inhibition [40,41]. PV expressing interneurons, which constitute 1-2% of NAc neurons, have particular firing properties and are classified as FS-neurons [40,42]. Other interneurons in the NAc that express somatostatin, neuropeptide Y, and neuronal nitric oxide synthase are classified as persistently low-threshold spiking (PLTS) neurons [42].…”
Section: Discussionmentioning
confidence: 99%